Participation of Farm Women in Land Use Decision Making Process - A CaseStudy in Panubali Watershed of Nagpur District, Maharashtra (Indian Journal of Extension Education, 2010)
Women plays a significant and crucial role in land use decision making process for agricultural development. Land use in agriculture and allied fields including crop production, livestock production, horticulture, post harvest operations, agro-social forestry and fisheries requires high managerial skill for rainsing farm income. The fact is that women’s managerial contribution in these sectors have either largely ignored or inadequately acknowledged. This posses a handicap in their becoming of equal partners in land management activities. Very few scientific and empirical attempts have been made to examine the actual participation of farm women in land use decision making process.